2014
DOI: 10.1038/jcbfm.2013.244
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microvascular Damage Occurs Early after Hypoxia–Ischemia via nNOS Activation in the Neonatal Brain

Abstract: Microvascular injury early after hypoxic ischemia (HI) may contribute to neonatal brain damage. N-methyl-D-aspartate receptor overstimulation activates neuronal nitric oxide synthases (nNOS). We hypothesized that microvascular damage occurs early post-HI via nNOS activation and contributes to brain injury. Postpartum day-7 rat pups were treated with 7-nitroindazole (7-NI) or aminoguanidine (AG) before or after HI. Electron microscopy was performed to measure neuronal and endothelial cell damage. There were vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…However, a similar vasoactive effect is also rapidly observed with 7-NI given after re-flow, suggesting that 7-NI, nevertheless, may have a direct and/or indirect role in collateral recruitment and patency in the P14 rat. Our data at P14 (with one dose of 7-NI) highlight those reported in the ischemic P7 rat pup (only demonstrated with US imaging [9] ), and in the hypoxic-ischemic P7 rat [10] . We cannot completely exclude that using others doses, this effect would be or not seen, because by using various doses of nNOS inhibitor(s), authors reported opposite effects (see the discussion in ref [25] ).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…However, a similar vasoactive effect is also rapidly observed with 7-NI given after re-flow, suggesting that 7-NI, nevertheless, may have a direct and/or indirect role in collateral recruitment and patency in the P14 rat. Our data at P14 (with one dose of 7-NI) highlight those reported in the ischemic P7 rat pup (only demonstrated with US imaging [9] ), and in the hypoxic-ischemic P7 rat [10] . We cannot completely exclude that using others doses, this effect would be or not seen, because by using various doses of nNOS inhibitor(s), authors reported opposite effects (see the discussion in ref [25] ).…”
Section: Discussionsupporting
confidence: 72%
“…In the adult brain, 7-NI significantly reduces arteriole dilation and prevents the increase in erythrocyte velocity and flux through capillaries (thus reducing hyperemia) during early reperfusion [12,24] . Interestingly, 7-NI significantly decreased microvascular nitrosative stress, improved patent vascular lumen, reduced blood-brain barrier damage, and increased cerebral perfusion in the neonatal model of hypoxia-ischemia [10] . As we report here that 7-NI did not reduce BF in the BT, our data also suggest that collateral supply may be originated in the occipital pole toward the distal segment of the MCA (penumbra).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhaled NO given during the reperfusion period appears to have neurotoxic effects (Charriaut-Marlangue et al, 2012). This may be due to the activation of nNOS as inhibition leads to improved CBF and perfusion early after reoxygenation (Hsu et al, 2014). As in the developed brain, iNOS activation may be responsible for damage in the late (N 24 h) phase (Higuchi et al, 1998).…”
Section: The Role Of Inosmentioning
confidence: 98%
“…For many other brain disorders, impaired vascular health seems at least partially to contribute to the damage. Hsu et al recently found that microvascular damage occurs early and progressively after neonatal HI, and interventions that reduced vascular injury also improved outcome (Hsu et al, 2014). Both animal and clinical studies have shown damage to the blood-brain barrier following neonatal HI, further indicating that these insults are associated with vascular damage (Kumar et al, 2008;Muramutsi et al, 1997).…”
mentioning
confidence: 93%